Experimental studies on islets isolation, purification and function in rats - Pang, Xinlu (Int J Clin Exp Med, 2015)
To develop a simple and effective method of islet isolation and purification in rats. Collagenase P was injected into pancreatic duct followed by incubation in water bath to digest the pancreas and isolate islet, then discontinuous gravity gradient purification was used to purify the islet. The purified islets were identified by dithizone staining. The viability of islets was assessed by fluorescence staining of acridine orange (AO) and propidium iodide (PI). The function of purified islets was determined by glucose-stimulated insulin release test and transplantation of rat with streptozocin-induced diabetes. 738±193 islets were recovered after purification. The average purity was 77±13%, the viability of islets was more than 95%. When inspected by glucose stimulation, the secreted insulin concentration was 24.31±5.47 mIU/L when stimulated by low concentration glucose and 37.62±4.29 mIU/L by high concentration glucose. There was significant difference between the two phases (P<0.05). The blood sugar concentration recovered to normal level after two days in the animals with islet transplantation. In conclusion, islets can be procured with good function and shape by using the method of injecting collagenase into pancreatic duct followed by incubation in water bath and purification using discontinuous gravity gradient.